Cardiac hemangioma of the right atrium - Zanati, Silmeia Garcia [UNESP]; Hueb, Joao Carlos [UNESP]; Cogni, Ana Lucia [UNESP]; Teixeira de Morais, Maria Gorete [UNESP]; Almeida Prado Franceschi, Luiz Eduardo de [UNESP]; Morceli, Mauricio [UNESP]; Cicogna, Antonio Carlos [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Oxford University Press, 2008)
Primary cardiac tumors are rare, with an incidence range between 0.001% and 0.030% at autopsy. Recent technical advances have facilitated diagnosis and surgical treatment of such lesions. Patients with a resectable tumor usually have a good prognosis, but patients with an unresectable tumor may have a poor prognosis. This report shows a case of right atrial hemangioma growing like an extracardiac mass, with cardiac tamponade the only clinical presentation.
Keywords: cardiac tumor; echocardiography; heart failure